Feasibility, safety, and efficacy of high-dose intermittent theta burst stimulation in children with autism spectrum disorder: study protocol for a pilot randomized sham-controlled trial - Long, Junzi; Niu, Maoyuan; Liao, Xingxing; Han, Kaiyue; Chen, Jiarou; Su, Wenlong; Wang, Xianna; Liu, Jianjun; Zhang, Yan; Zhang, Hao (Frontiers in Psychiatry, 2025)
BackgroundAutism spectrum disorders (ASD) are common neurodevelopmental disorders, mainly caused by disrupted excitation/inhibition balance and synaptic plasticity. Intermittent theta burst stimulation (iTBS) is a variant of excitatory repetitive transcranial magnetic stimulation, inducing long-term potentiation-like plasticity. In recent years, there has been a growing interest in high-dose iTBS as a therapeutic tool for psychiatric disorders. We aim to preliminarily investigate the feasibility, safety, and efficacy of high-dose iTBS in children with autism spectrum disorder (ASD).MethodsA randomized controlled pilot trial with a 4-week intervention will be conducted. Forty children with ASD will be randomized into either the intervention or control group. The intervention group will receive 5400-pulse iTBS per day, while the control group will receive sham iTBS. Feasibility will be evaluated through recruitment, intervention adherence, and assessment completion. Safety will be assessed by comparing the rates of drop-outs attributed to adverse events and the rates of serious adverse events The efficacy outcomes include the Autism Behavior Checklist, Social Responsiveness Scale, 2nd Edition, Childhood Autism Rating Scale, Autism Treatment Evaluation Checklist and Repetitive Behavior Scale-Revised. Resting-state electroencephalogram and functional near-infrared spectroscopy will be employed to quantify alterations in functional brain connectivity and cerebral haemodynamics. Salivary levels of oxytocin, growth hormone, insulin-like growth factor 1, and insulin-like growth factor binding protein 3 are measured to reflect the biochemical response to iTBS. These indicators will be assessed at baseline and at the end of the intervention.DiscussionThis trial will evaluate the feasibility, safety, and efficacy of high-dose iTBS treatment in children with ASD. The proposed study will provide pilot data to inform the feasibility and design of larger sample-size trials.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2400089757.